The dynamics of social deprivation in Mexico - José Carlos Ramírez; Vivian Kadelbach; Leovardo Mata (Latin American Economic Review, 2021)
This paper aims to model the dynamics of social deprivation in Mexico using a Markovian approach. First, we establish a scenario where a list of items characterizing social deprivation evolves as a first-order Markov chain under the sample period (2002-2012). Then, we estimate latent states and ergodic vectors of a hidden-Markov model to verify the strength of the conclusions drawn from such a scenario. After collecting results from both kinds of analyses, we find a similar pattern of impoverishment. The paper's conclusions state that the evolution of Mexico's deprivation profile may slightly worsen soon.
Keywords: C15; I32; 330; Hidden and direct Markov models; Mexico's social deprivation; poverty profile; latent states; ergodic vectors